Complicating Conscience, Refreshing Discontent (Diametros, 2016)
The 19th Century New England author Thoreau provides an approach to conscience and unjust laws approximating that given by St. Thomas Aquinas in Summa Theologiae. But the portrait of conscience given by Thoreau in the 1848 oration “Civil Disobedience” is incomplete. Thoreau’s approach is solved by accepting insights given in Part I and Part I–II of Summa Theologiae. Allowing St. Thomas’ insights requires reform of Thoreau’s civil disobedience and conscientious objection. But Thoreau’s arguments are given new life.